Supply-Side Modeling from Bits and Pieces - Furstenberg, George M. von; Green, R Jeffrey (American Economic Review, 1986)
As the history of Keynesianism illustrates, the distinguishing features and exact claims associated with a particular economic policy doctrine are rarely clear in the early stages of its development. Supply-side economics is no different. Like Keynesianism it has received political applications before its content was settled. Thus, expository work remains to be done before supply-side economics is likely to attract the detailed attention and criticism that will ultimately define its place in the policy discussions of our discipline. To help place the new approach to economic policy, this paper selects some properties and conditions that could be consonant with major aspects of supply-side doctrine. In preparing this selection, we are quite indifferent to whether those from whose thoughts or models we pick are professed supply siders. Furthermore only two of several possible points of distinction are developed. The first theme we wish to elucidate is that supply siders insist, more than most economists, that policy should be conducted by rules relating not to procedure (stable money growth), but objectives (stable prices). Procedural rules (tax indexing) or constitutional restraints (balanced budget) may be resorted to as a second-best. Such positions may be advocated if the feedback control mechanisms involved in gearing economic policy instruments directly to final targets are prevented from functioning reliably in the existing political system. In general, however, supply-side economics presents itself as firm and principled on targets, but flexible on methods. The second point is that, to appreciate the elasticity optimism which brought supply-side economics to public attention in the first place, the short run should be extended to one generation and the long run to several generations. The overall impression we hope to convey is that even though supply-side economics has lacked a dominant intellect as challenging as Keynes was to Keynesians and non-Keynesians alike, it may have something beyond mere variations in emphasis to contribute to the concerns of economic policy.